Model Mini Research Perkembangan Individu Dalam Mengembangkan Keterampilan Berpikir Tingkat Tinggi - Eli Karliani; Triyani (FKIP, Universitas Palangka Raya, 2021)
This study aims to develop, implement, and evaluate a mini research model of observing individual development in developing higher-order thinking skills. The method used descriptive qualitative research. Qualitative research data were obtained from the observation sheet on the achievement of the learning process which included the teaching activity observation sheet for lecturers, and the observation sheet for student learning activities, and the assessment of the results of the mini research model. The Results of mini research activities were carried out with group activities in teaching services, surveys, observations, and interviews. Mini research products include: 1) Physical development: average height, weight, puberty for boys and girls; 2) Cognitive development can be seen from the understanding of the values ​​of Pancasila; 3) Emotional and moral development can be seen in attitudes and behavior in accordance with the appropriateness of the prevailing norms; 4) Social development can be seen in the social attitudes of adolescents interacting with others. The achievement of applying the teaching steps of the lecturer with the mini research model has an average achievement of 85.6%. The achievement of student learning activities with the mini research model has an average of 81.4%.